Identifikasi Masalah Usability pada Aplikasi Mobile Halodoc dengan Menggunakan Metode Usability Testing - Luthfi Irfan Hakim Praditya; Hanifah Muslimah Az-Zahra; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The Halodoc mobile application on the Google Playstore was recorded as of January 2021 getting a rating of 4.8 out of 5 with around 6 thousand users still giving a rating of 1. Halodoc prioritizes the ease of consulting with doctors through chat features with doctors, purchasing drugs, making hospital appointments and visit without the need to queue. Based on user feedback and preliminary interviews with the Halodoc application, it was found that there were difficulties in finding information and felt uncomfortable with the display of images that were deemed unrepresentative, there were also a complaint to the displays on some of the menus. These constraints cause a sense of discomfort to the user. To find out how comfortable the user feels when using an application, an evaluation of the usability of the application is needed. Based on the evaluation of usability testing to three new user participants and three old user participants from the Halodoc application, a proposed design design was then made as a recommendation for improvement based on the design principles of the Eight Golden Rules. The results of the evaluation of the proposed design get an increase in the usability value, namely the learnability criterion of 1.62 which decreases to 1.13. Efficiency criteria of 89.97% increased to 100.0%. The criteria for memorability are the average number of steps and average clicks from 33 steps and 29.33 clicks to 27.33 steps and 23.33 clicks. The errors criteria got a value of 6.48%, decreased to 0%, and the satisfaction criteria got a value of 81.3 which increased to 90,8 which means it is also above the average score. With the test results that have increased from the usability value, the proposed design can be easily used by users and has resolved user problems.